Filamin A increases aggressiveness of human neuroblastoma. Issue 1 (28th February 2022) - Bandaru, Sashidar; Prajapati, Bharat; Juvvuna, Prasanna Kumar; Dosa, Sandor; Kogner, Per; Johnsen, John I; Kanduri, Chandrasekhar; Akyürek, Levent M
Abstract: Background: The actin-binding protein filamin A (FLNA) regulates oncogenic signal transduction important for tumor growth, but the role of FLNA in the progression of neuroblastoma (NB) has not been explored. Methods: We analyzed FLNA mRNA expression in the R2 NB-database and FLNA protein expression in human NB tumors. We then silenced FLNA expression in human SKNBE2 and IMR32 NB cells by lentiviral vector encoding shRNA FLNA and assayed the cells for proliferation, migration, colony, spheroid formation, and apoptosis. SKNBE2 xenografts expressing or lacking FLNA in BALB/c nude mice were analyzed by both routine histopathology and immunohistochemistry. Results: We observed shorter patient survival with higher expression of FLNA mRNA than patients with lower FLNA mRNA expression, and high-risk NB tumors expressed higher FLNA levels. Overexpression of FLNA increased proliferation of SH-SY5 NB cells. NB cell lines transfected with siRNA FLNA proliferated and migrated less, expressed lower levels of phosphorylated AKT and ERK1/2, formed smaller colonies and spheroids, as well as increased apoptosis. After inoculation of SKNBE2 cells infected with lentivirus expressing shRNA FLNA, size of NB tumors and number of proliferating cells were decreased. Furthermore, we identified STAT3 as an interacting partner of FLNA. Silencing FLNA mRNA reduced levels of NF-κB, STAT3 and MYCN, and increased levels of p53 and cleaved caspase 3. Conclusion: Inhibition of FLNA impaired NB cell signaling and function and reduced NB tumor size in vivo, suggesting that drugs targeting either FLNA or its interaction with STAT3 may be useful in the treatment of NB.